A preparation method of a composite photoelectrode and its product and application

By depositing a polyethylene glycol layer on the surface of BiVO4 photoelectrode to form a composite photoelectrode, the problem of poor carrier separation and transmission performance of BiVO4 photoanode is solved, and its photoelectrochemical performance and stability are significantly improved.

CN118800593BActive Publication Date: 2025-05-02GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410854814.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-05-02
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

The pure BiVO4 photoanode has poor carrier separation and transmission performance in photoelectrochemical water decomposition, resulting in its actual performance far lower than the theoretical value.

Method used

Bismuth vanadate (BiOI) thin films were deposited in sequence on a conductive glass fluorine-doped tin oxide (FTO) substrate and calcined to obtain a BiVO4 photoelectrode, and then a polyethylene glycol (PEG) layer was deposited on the surface of the BiVO4 photoelectrode to form a composite photoelectrode.

Benefits of technology

This method significantly improves the carrier separation efficiency of bismuth vanadate photoelectrode, improves photoelectrochemical performance, and enhances the stability of the photoanode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118800593B_ABST
    Figure CN118800593B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method, product and application of a composite photoanode, belonging to the technical field of photoelectrochemical analysis. Through an in-situ photopolymerization method, using fluorine-doped tin oxide conductive glass as a substrate, the substrate is successively modified with bismuth vanadate and polyethylene glycol, and a bismuth vanadate layer and a polyethylene glycol layer are successively formed on the surface of the substrate, thereby obtaining the composite photoanode. This composite photoanode can quickly conduct away the electrons and holes separated under light illumination, reduce recombination, passivate the interface defects of BiVO4, and improve the photoelectric performance of the photoanode. This method is simple and safe to operate, the materials are easily available, and large-scale production can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photoelectrochemical analysis, and in particular relates to a preparation method of a composite photoelectrode and a product and application thereof. Background Art

[0002] Solar energy has received widespread attention in solving the energy crisis, and how to convert solar energy into fuel that can be used by humans and is easy to store is a key challenge. Photoelectrochemical (PEC) water splitting can directly convert solar energy into hydrogen energy that is easy to store, and is the most promising method for utilizing solar energy. Photoelectrochemistry is an electrochemical process under the action of light, that is, under light conditions, electrons transition from the ground state to the excited state, thereby generating electron transfer. Therefore, photoelectrochemical reactions can be used to convert light energy into chemical energy and electrical energy.

[0003] Recently, BiVO 4 It has attracted extensive attention as a photoanode material for PECs because it has a suitable band structure with a band gap of 2.40-2.50 eV and a favorable conduction band edge position (≈0.1 eV) that is conducive to H 2 The maximum photocurrent density is estimated to be 7.5 mA cm -2 , the theoretical conversion efficiency of solar energy to hydrogen is 9.2%. However, pure BiVO 4 The actual performance of the photoanode is much lower than the theoretical value because it has inherent disadvantages such as weak light absorption, poor separation and transport of photogenerated carriers, and poor surface catalytic oxygen production kinetics. 4 Modification to make it have stronger photogenerated carrier transport ability and good stability is an important issue to be solved at present. Summary of the invention

[0004] In view of the above technical problems, the present invention proposes a preparation method of a composite photoelectrode and its product and application to solve the problem of traditional BiVO 4 The present invention uses conductive glass fluorine-doped tin oxide (FTO) as a substrate, and sequentially modifies it with bismuth vanadate and polyethylene glycol (PEG), so that polyethylene glycol is attached to the surface of bismuth vanadate as a hole transport layer, so as to achieve the purpose of improving the performance of bismuth vanadate photoelectrode while protecting bismuth vanadate, so that bismuth vanadate-polyethylene glycol composite photoelectrode has high carrier separation efficiency.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a composite photoelectrode, using a conductive glass fluorine-doped tin oxide as a substrate by in-situ photopolymerization, sequentially modifying the substrate with bismuth vanadate and polyethylene glycol, sequentially forming a bismuth vanadate layer and a polyethylene glycol layer on the surface of the substrate, and obtaining a composite photoelectrode. The specific preparation method includes the following steps:

[0007] Dissolving potassium iodide in a nitric acid solution, adding bismuth nitrate pentahydrate, and stirring to obtain a solution A; dissolving p-benzoquinone in ethanol to obtain a solution B; stirring and mixing the solution A and the solution B to obtain an electrolyte; and depositing the electrolyte on a conductive glass fluorine-doped tin oxide to form a BiOI film by an electrochemical method;

[0008] Vanadyl acetylacetonate is dissolved in a dimethyl sulfoxide solution and dripped onto the surface of the BiOI film, annealed, and then immersed in a NaOH solution, rinsed with water, and dried to obtain BiVO 4 Photoelectrode;

[0009] The ethylene glycol solution is dissolved in tertiary water to obtain an electrolyte, and the electrolyte is deposited on the BiVO 4 On the photoelectrode, a composite photoelectrode containing a bismuth vanadate layer and a polyethylene glycol layer is obtained.

[0010] Furthermore, the deposition parameters in the process of preparing the BiOI film are: initial voltage -0.1 V, sampling interval 0.1 s, deposition time 150-200 s, standing time 0 s (indicating the waiting time before deposition, 0 s means no waiting, the same below), sensitivity 1×10 -3 A.

[0011] Furthermore, the electrochemical method used in the preparation of the BiOI film is a time-current curve method, with conductive glass fluorine-doped tin oxide as the working electrode, a platinum mesh as the counter electrode, and an Ag / AgCl electrode as the reference electrode.

[0012] Furthermore, the parameters of the annealing treatment are: temperature 430-480°C, heating rate 2°C / min, and time 2h.

[0013] Furthermore, the deposition parameters in the process of preparing the composite photoelectrode are: initial voltage 0V, sampling interval 0.1s, deposition time 600s, standing time 0s, sensitivity 1×10 -5 A.

[0014] Furthermore, the electrochemical method used in the preparation of the composite photoelectrode is a time-current curve method, with BiVO 4 The photoelectrode is the working electrode, the platinum mesh is the counter electrode, the Ag / AgCl electrode is the reference electrode, and the light intensity is 100 mW / cm 2 .

[0015] A composite photoelectrode prepared by the above preparation method.

[0016] An application of the composite photoelectrode in the field of photoelectrochemistry.

[0017] Compared with the prior art, the present invention has the following advantages and technical effects:

[0018] 1) The present invention uses conductive glass doped with fluorine-doped tin oxide as a substrate, deposits a BiOI film by an electrochemical method, and obtains BiVO after calcination. 4 The photoelectrode was then used to deposit polyethylene glycol on BiVO 4 The photoelectrode surface is easy and safe to operate, the materials are readily available, and large-scale production can be achieved;

[0019] 2) The present invention uses in-situ photopolymerization on BiVO 4 The synthesized polyethylene glycol layer, as a hole transport layer, passivates the surface state, promotes the transport of carriers, reduces the recombination of surface charges, and greatly improves the performance of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0021] Figure 1 is the BiVO in Example 1 4 Scanning electron microscope (SEM) image of the photoelectrode;

[0022] Figure 2 The FTO conductive glass and BiVO in Example 1 4 Photoelectrodes and PEG / BiVO 4 X-ray diffraction (XRD) pattern of the composite photoelectrode;

[0023] Figure 3 PEG / BiVO in Example 1 4 Scanning image of the composite photoelectrode under a transmission electron microscope (TEM);

[0024] Figure 4 PEG / BiVO in Example 1 4 Fourier transform infrared spectrometer (FTIR) image of the composite photoelectrode;

[0025] Figure 5 PEG / BiVO in Example 1 4 Comparison of photoluminescence spectra (PL) of composite photoelectrodes;

[0026] Figure 6For BiVO in the presence of hole traps 4 and PEG / BiVO 4 Comparison of linear sweep voltammetry curves of composite photoanodes;

[0027] Figure 7 For BiVO without hole trapping agent 4 and PEG / BiVO 4 Comparison of linear sweep voltammetry curves of composite photoanodes. DETAILED DESCRIPTION

[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0033] In the composite photoelectrode prepared by the present invention, polyethylene glycol is attached to the surface of bismuth vanadate and serves as a hole transport layer. The composite photoelectrode can quickly conduct away the electrons and holes separated under light, reduce recombination, and passivate BiVO 4The interface defects are eliminated, and the photoelectric performance of the photoanode is improved. The method adopted by the invention is simple and safe to operate, and the materials are readily available, and large-scale production can be realized.

[0034] The present invention prepares a composite photoelectrode by in-situ photopolymerization. The photoanode is layered and includes FTO conductive glass. BiVO 4 The preparation method of the composite photoelectrode comprises the following steps:

[0035] 1) dissolving potassium iodide in a nitric acid solution, then adding bismuth nitrate pentahydrate and stirring to obtain a solution A; dissolving p-benzoquinone in ethanol to obtain a solution B; fully stirring and mixing the solution A and the solution B to obtain an electrolyte; using an electrochemical method to deposit the electrolyte on the FTO conductive glass to form a BiOI film;

[0036] 2) The FTO conductive glass prepared in step 1) and deposited with the BiOI film is placed flat in a muffle furnace, vanadium acetylacetonate is dissolved in a dimethyl sulfoxide solution and dripped on the surface of the BiOI film, annealed at 430-480° C. (preferably 450° C.), immersed in a NaOH solution after annealing, rinsed with water, and dried to obtain BiVO 4 Photoelectrode;

[0037] 3) dissolving the ethylene glycol solution in grade tertiary water to obtain an electrolyte; using an electrochemical method to prepare the BiVO 4 Photoelectric deposition is carried out on the photoelectrode to obtain a composite photoelectrode of bismuth vanadate and polyethylene glycol.

[0038] In step 1) of the following embodiment of the present invention, the specific preparation method of the electrolyte is:

[0039] A. Take 25 mL of nitric acid solution with a pH of 1.6-1.8 (preferably pH=1.7), add 0.4 M potassium iodide and 0.04 M bismuth nitrate pentahydrate, and stir thoroughly to obtain solution A;

[0040] B. Take 10 mL of ethanol, add 0.23 M p-benzoquinone, and sonicate for 5 min to obtain solution B;

[0041] C. Mix solution A and solution B and stir thoroughly to obtain an electrolyte.

[0042] In step 1) of the following embodiment of the present invention, the electrochemical method is the time-current curve method, with FTO conductive glass as the working electrode, platinum mesh as the counter electrode, and Ag / AgCl electrode as the reference electrode. The process parameters for depositing BiOI thin film on FTO conductive glass with electrolyte are: initial voltage -0.1V, sampling interval 0.1s, deposition time 150-200s (preferably 180s), standing time 0s, sensitivity 1×10-3 A.

[0043] In step 2) of the following example of the present invention, the concentration of NaOH is 1 M. The specific operation of dissolving vanadium acetylacetonate in dimethyl sulfoxide solution is as follows: take 2 ml of dimethyl sulfoxide and add 0.2 M vanadium acetylacetonate.

[0044] In step 3) of the following embodiment of the present invention, the specific preparation method of the electrolyte is: take 50 mL of tertiary water, add 0.1 M ethylene glycol, and perform ultrasound for 5 minutes to obtain the electrolyte.

[0045] In step 3) of the following embodiment of the present invention, the electrochemical method is a time-current curve method, with BiVO 4 The photoelectrode is the working electrode, the platinum mesh is the counter electrode, the Ag / AgCl electrode is the reference electrode, and the light intensity is 100 mW / cm 2 . Using electrolyte B in BiVO 4 The process parameters for photoelectrodeposition on the photoelectrode are: initial voltage 0 V, sampling interval 0.1 s, deposition time 600 s, rest time 0 s, sensitivity 1 × 10 -5 A.

[0046] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0047] The raw materials used in the present invention are all purchased from the market.

[0048] The technical solution of the present invention is further illustrated by the following embodiments.

[0049] Example 1

[0050] A method for preparing a composite photoelectrode comprises the following steps:

[0051] S1、BiVO 4 Preparation of photoelectrode:

[0052] 1) Pretreatment of FTO conductive glass: Take a piece of FTO conductive glass of 20×15 cm, cut it into 2×3 cm specifications with a glass cutting table, and ultrasonically wash it with acetone, ethanol, and three-grade water for 15 minutes in sequence. After washing, put it in an oven for drying;

[0053] 2) Preparation of electrolyte: Take 25 mL of nitric acid solution with a pH of 1.7, add 0.4 M potassium iodide (KI) and 0.04 M bismuth nitrate pentahydrate (Bi(NO 3 ) 3 ·5H 2O), stirring thoroughly until the solution is clear and transparent to obtain solution A; taking 10mL of anhydrous ethanol and placing it in a beaker, adding 0.23M p-benzoquinone, and ultrasonicating for 5min until the precipitate is completely dissolved to obtain solution B; mixing solution A and solution B and stirring vigorously to make them fully miscible to obtain an electrolyte;

[0054] 3) The time-current curve method was selected, with the 2×3 cm FTO conductive glass dried in step 1) as the working electrode, the platinum mesh as the counter electrode, the Ag / AgCl as the reference electrode, the initial voltage of -0.1 V, the sampling interval of 0.1 s, the deposition time of 180 s, the standing time of 0 s, and the sensitivity of 1×10 -3 A, electro-depositing the electrolyte obtained in step 2) onto the substrate FTO conductive glass to form a BiOI film on the surface of the FTO conductive glass; rinsing with grade tertiary water, drying, obtaining the FTO conductive glass deposited with the BiOI film, and then cutting it into a size of 2×1 cm using a glass cutting table;

[0055] 4) Place FTO conductive glass with BiOI thin film deposited on a high temperature resistant corundum sheet with a size of 2×1 cm, leaving a certain distance of 2-4 mm between the sheets;

[0056] Take 2mL of dimethyl sulfoxide (DMSO), add 0.2M acetylacetonatovanadium, stir vigorously until there is no obvious precipitation, use a 100μL pipette to take 60μL of the resulting solution and evenly drip it on the surface of the BiOI film, then slowly place the corundum sheet in a muffle furnace, heat it to 450℃ at a heating rate of 2℃ / min, calcine for 2h, wait for the muffle furnace to cool to room temperature, slowly take out the corundum sheet, place the fired FTO conductive glass in a watch glass, add an appropriate amount of 1M NaOH solution, and soak it for 15-25min to remove excess V 2 O 5 The surface of the FTO conductive glass obtained is complete and uniform, and bright yellow; after three-level water washing and drying, BiVO 4 Photoelectrode;

[0057] S2、PEG / BiVO 4 Preparation of composite photoelectrodes

[0058] 1) Preparation of electrolyte: Take 50 mL of grade tertiary water and add 0.1 M ethylene glycol (C 2 H 6 O 2 ), stirring for 5 min to obtain an electrolyte;

[0059] 2) Using the time-current curve method, BiVO 4 The photoelectrode is the working electrode, the platinum mesh is the counter electrode, the Ag / AgCl electrode is the reference electrode, and the light intensity is 100 mW / cm2 , initial voltage is 0 V, sampling interval is 0.1 s, deposition time is 600 s, rest time is 0 s, sensitivity is 1 × 10 -3 A, the electrolyte obtained in step 1) is electrodeposited onto BiVO 4 After the deposition was completed, the surface of the photoelectrode was rinsed with grade III water and heated on a heating plate at 60 °C for 10 min to obtain a composite photoelectrode of bismuth vanadate and polyethylene glycol (also known as PEG / BiVO 4 ).

[0060] Figure 1 is the BiVO in Example 1 4 Scanning electron microscope (SEM) image of the photoelectrode; Figure 1 As can be seen, BiVO 4 The photoelectrode electrodes were successfully prepared.

[0061] Figure 2 The FTO conductive glass and BiVO in Example 1 4 Photoelectrodes and PEG / BiVO 4 X-ray diffraction (XRD) pattern of the composite photoelectrode; Figure 2 As can be seen, BiVO 4 Photoelectrodes and PEG / BiVO 4 The composite photoelectrode was successfully prepared.

[0062] Figure 3 PEG / BiVO in Example 1 4 Scanning image of the composite photoelectrode under a transmission electron microscope (TEM); it can be seen that polyethylene glycol is on BiVO 4 A polymer film is formed on the surface, which indicates that PEG has attached to BiVO 4 On the photoelectrode.

[0063] Figure 4 PEG / BiVO in Example 1 4 Fourier transform infrared spectrometer (FTIR) image of the composite photoelectrode; this image further confirms that PEG has been attached to BiVO 4 Photoelectrode surface.

[0064] Figure 5 PEG / BiVO in Example 1 4 Comparison of photoluminescence spectra (PL) of the composite photoelectrode; the horizontal axis represents the wavelength and the vertical axis represents the emission intensity. 4 In comparison, PEG loaded BiVO 4 The emission intensity of the prepared PEG / BiVO 4 Composite photoelectrodes can suppress the recombination of charge carriers.

[0065] Figure 6 In the presence of 0.5 M Na 2 SO 3 BiVO in boric acid solution (PH = 9.5) containing hole trapping agent 4 and PEG / BiVO 4 Comparison of linear scanning voltammetry curves of composite photoanodes; the horizontal axis represents voltage, and the vertical axis represents current density. It can be seen that under the test conditions with hole capture agent, after loading PEG, PEG / BiVO 4 The composite photoelectrode can achieve a higher photocurrent density. When the light source is not turned on, it is a dark test environment.

[0066] Figure 7 For the absence of 0.5M Na 2 SO 3 PEG / BiVO in boric acid solution (PH = 9.5) containing hole trapping agent 4 Comparison of linear sweep voltammetric curves of composite photoanodes. The horizontal axis represents voltage, and the vertical axis represents current density. Under the test conditions without hole trapping agent, after adding PEG layer, PEG / BiVO 4 The photocurrent of the electrodes has been significantly improved. At 1.23V (vs. RHE), the photocurrent increased by 1.4 times. The dark test environment is when the light source is not turned on.

[0067] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a composite photoelectrode, characterized in that: The following steps are involved: Dissolving potassium iodide in a nitric acid solution, adding bismuth nitrate pentahydrate, and stirring to obtain a solution A; dissolving p-benzoquinone in ethanol to obtain a solution B; stirring and mixing the solution A and the solution B to obtain an electrolyte; and depositing the electrolyte on a conductive glass fluorine-doped tin oxide to form a BiOI film by an electrochemical method; Dissolving vanadium acetylacetonate in a dimethyl sulfoxide solution and dripping it on the surface of the BiOI film, annealing it, soaking it in a NaOH solution after annealing, washing it with water, and drying it to obtain a BiVO4 photoelectrode; Dissolving an ethylene glycol solution in grade tertiary water to obtain an electrolyte, and depositing the electrolyte on the BiVO4 photoelectrode by an electrochemical method to obtain a composite photoelectrode containing a bismuth vanadate layer and a polyethylene glycol layer; The deposition parameters in the process of preparing the composite photoelectrode are: initial voltage 0 V, sampling interval 0.1 s, deposition time 600 s, standing time 0 s, sensitivity 1×10 -5 A; The electrochemical method used in the preparation of the composite photoelectrode is the time-current curve method, with BiVO4 photoelectrode as the working electrode, platinum mesh as the counter electrode, Ag / AgCl electrode as the reference electrode, and the light intensity of 100 mW / cm 2 ; The concentration of ethylene glycol in the electrolyte is 0.1M.

2. The method for preparing the composite photoelectrode according to claim 1, characterized in that: The deposition parameters in the process of preparing the BiOI film are: initial voltage -0.1 V, sampling interval 0.1 s, deposition time 150-200 s, standing time 0 s, sensitivity 1×10 -3 A.

3. The method for preparing the composite photoelectrode according to claim 1, characterized in that: The electrochemical method used in the preparation of the BiOI film is a time-current curve method, with conductive glass fluorine-doped tin oxide as the working electrode, a platinum mesh as the counter electrode, and an Ag / AgCl electrode as the reference electrode.

4. The method for preparing the composite photoelectrode according to claim 1, characterized in that: The parameters of the annealing treatment are: temperature 430-480° C., heating rate 2° C. / min, and time 2 h.

5. A composite photoelectrode prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the composite photoelectrode as claimed in claim 5 in the field of photoelectrochemistry.